1989
DOI: 10.1159/000195783
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Tracheobronchial Clearance in Healthy Non-Smoking Subjects

Abstract: Tracheobronchial clearance was measured twice in 10 healthy non-smoking volunteers to evaluate inter- and intrasubject variability, using a radio-aerosol technique (5 μm 99mTc-labelled polystyrene particles). By means of two detectors radioactivity in the lungs was measured at regular intervals for 6 h and once more 24 h after inhalation. The decrease in radioactivity after correction for background activity, isotope decay and 24-hour retention was assumed to reflect tracheobronchial clearance. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Labeled polystyrene microspheres given by inhalation have also been used in human studies for measurement of mucociliary clearance rates and airway resistance (17)(18)(19)(20)(21)(22). In our study, there was no evidence of penetration and accumulation of microspheres within extrapulmonary organs.…”
Section: Total Cell Counts % Macrophages % Neutrophils and Microspmentioning
confidence: 51%
“…Labeled polystyrene microspheres given by inhalation have also been used in human studies for measurement of mucociliary clearance rates and airway resistance (17)(18)(19)(20)(21)(22). In our study, there was no evidence of penetration and accumulation of microspheres within extrapulmonary organs.…”
Section: Total Cell Counts % Macrophages % Neutrophils and Microspmentioning
confidence: 51%
“…PSL particles have been used extensively to study translocation, clearance, and ventilation in both human and animal lungs. [40][41][42][43][44][45] These, and similar studies with other types of particles, 46,47 show that the translocation of nanoparticles to other organs is very limited for particles in the range 40-100 nm. In-vitro studies with human lung cells exposed to PSL particles showed indistinguishable effects from controls.…”
Section: Dovepressmentioning
confidence: 91%